Saúde docente: relação entre gênero e estresse profissional - Bondan, Alzira Pimentel (2011)
The present study on Health Teacher: Relation between genre and professional stress is part of the research line Individual and Education , which studies education as a broad process involved in developing, training and self-education of individual, highlighting its interlacements with health, spirituality and life stories. The aim of this study is to analyze the health of teachers, focusing on stress at work, lived in their day to day relationship with the genres in order to understand how teachers male and female face these stresses. The methodology applied was qualitative approach, using as a research strategy the semi- structured interview, consisting of 12 questions that were imposed on teachers in a private school of Porto Alegre. The selected subjects (five men and five women) are the final years of teaching elementary and high school, because this is where education levels are teachers of both sexes. Data analysis was theoretically supported, textual analysis of discursive Galiazzi and Moraes (1997) in which the understanding of the texts was made through a systematic language by three main factors that guide this type of analysis: unitarization, categorization and communication. The categories that emerged were: Teacher training and development; strengths of the teaching profession; difficulties encountered in the development of teaching, teaching situations of stress and coping strategies, school and teacher health, genre differences in the development of teachers stress . This study did not intend to prove, or create a theory, however, through it was possible to consider that men are less involved with the issues of the students, dealing with situations with more distance, while women seek solutions and are concerned with much more immediate resolution of the issues, taking more the problems.